2019
DOI: 10.1038/s41467-019-10042-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting lonidamine to mitochondria mitigates lung tumorigenesis and brain metastasis

Abstract: Lung cancer often has a poor prognosis, with brain metastases a major reason for mortality. We modified lonidamine (LND), an antiglycolytic drug with limited efficacy, to mitochondria-targeted mito-lonidamine (Mito-LND) which is 100-fold more potent. Mito-LND, a tumor-selective inhibitor of oxidative phosphorylation, inhibits mitochondrial bioenergetics in lung cancer cells and mitigates lung cancer cell viability, growth, progression, and metastasis of lung cancer xenografts in mice. Mito-LND blocks lung tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
174
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(178 citation statements)
references
References 58 publications
4
174
0
Order By: Relevance
“…Several studies have reported drug delivery systems for the transport of anticancer compounds to the mitochondria [18], highlighting the use of the lipophilic cations pyridinium [53][54][55] and TPP + [56][57][58][59]. In particular, we showed that TPP + derivatives of gallic acid and GA selectively induce cell death in BC cells [19,20] in a receptor status-independent manner [20] without toxic effects on nontumoral tissues in vivo [21].…”
Section: Discussionmentioning
confidence: 74%
“…Several studies have reported drug delivery systems for the transport of anticancer compounds to the mitochondria [18], highlighting the use of the lipophilic cations pyridinium [53][54][55] and TPP + [56][57][58][59]. In particular, we showed that TPP + derivatives of gallic acid and GA selectively induce cell death in BC cells [19,20] in a receptor status-independent manner [20] without toxic effects on nontumoral tissues in vivo [21].…”
Section: Discussionmentioning
confidence: 74%
“…These mitocans failed to prove themselves in terms of sensitivity and efficacy in the latter stage of clinical trials. On the other side, Mito-LND and NSC13062 are the compounds that have the preliminary evidence of affecting the mitochondria of cancer cells and are proposed as possible mitocans [ 112 , 113 , 114 , 115 , 116 ]. Table 1 a,b enlist some widely studied synthetic mitocans, their class, and associated studies.…”
Section: Mitocans: the Alternative Cancer Therapymentioning
confidence: 99%
“…Notably, the anticancer drug lonidamine (LND) has been reported to inhibit complex II, and to increase the overall treatment response in cancer patients in combination with standard-of-care drugs, e.g., doxorubicin [35,36]. However, LND showed limited efficiency in clinical phase 3 trials but was recently modified into mito-lonidamine (Mito-LND), which is 100-fold more potent in cell culture and mouse models, and inhibits complex I and II [31].…”
Section: The Mitochondrial Electron Transport Chainmentioning
confidence: 99%